A tissue engineering approach for periodontal regeneration based on a biodegradable double-layer scaffold and adipose-derived stem cells - Requicha, J. F. (2014)
Human and canine periodontium are often affected by an inflammatory pathology called periodontitis, which isassociated with severe damages across tissues, namely, in the periodontal ligament, cementum, and alveolarbone. However, the therapies used in the routine dental practice, often consisting in a combination of differenttechniques, do not allow to fully restore the functionality of the periodontium. Tissue Engineering (TE) appearsas a valuable alternative approach to regenerate periodontal defects, but for this purpose, it is essential todevelop supportive biomaterial and stem cell sourcing/culturing methodologies that address the complexity ofthe various tissues affected by this condition. The main aim of this work was to study the in vitro functionalityof a newly developed double-layer scaffold for periodontal TE. The scaffold design was based on a combinationof a three-dimensional (3D) fiber mesh functionalized with silanol groups and a membrane, both made of ablend of starch and poly-e-(caprolactone). Adipose-derived stem cells (canine adipose stem cells [cASCs]) wereseeded and cultured onto such scaffolds, and the obtained constructs were evaluated in terms of cellularmorphology, metabolic activity, and proliferation. The osteogenic potential of the fiber mesh layer functionalizedwith silanol groups was further assessed concerning the osteogenic differentiation of the seeded andcultured ASCs. The obtained results showed that the proposed double-layer scaffold supports the proliferationand selectively promotes the osteogenic differentiation of cASCs seeded onto the functionalized mesh. Thesefindings suggest that the 3D structure and asymmetric composition of the scaffold in combination with stemcells may provide the basis for developing alternative therapies to treat periodontal defects more efficiently.